2018
DOI: 10.1016/j.vaccine.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians’ experience with zoster vaccine live (ZVL) and awareness and attitudes regarding the new recombinant zoster vaccine (RZV)

Abstract: Background: The Advisory Committee on Immunization Practices (ACIP) has routinely recommended zoster vaccine live (ZVL) for adults ≥60 since 2008; only 33% of eligible adults received it by 2016. A recombinant zoster vaccine (RZV) was licensed in 2017 and ACIP recommended in January 2018. Our objectives were to assess among primary care physicians 1) practices and attitudes regarding ZVL and 2) awareness of RZV. Methods: We administered an Internet and mail survey from July to September 2016 to national netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Although the Healthy People 2020 target was achieved, approximately 65% of adults recommended to receive this vaccine remain unprotected. Barriers that might have constrained overall herpes zoster vaccination uptake include shortages of herpes zoster vaccines (e.g., there was a ZVL shortage in 2011 and a RZV shortage in 2018) as well as financial and logistic challenges ( 44 , 45 ). The high cost for providers to purchase a supply and high out-of-pocket costs for patients are well-documented barriers ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Healthy People 2020 target was achieved, approximately 65% of adults recommended to receive this vaccine remain unprotected. Barriers that might have constrained overall herpes zoster vaccination uptake include shortages of herpes zoster vaccines (e.g., there was a ZVL shortage in 2011 and a RZV shortage in 2018) as well as financial and logistic challenges ( 44 , 45 ). The high cost for providers to purchase a supply and high out-of-pocket costs for patients are well-documented barriers ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eight weeks has also been the standard used in physician surveying to rapidly investigate emerging vaccine policy-relevant policy making by the Centers for Disease Control and Prevention. 19,[47][48][49][50] The simulation findings also show the value of graphing response curves over time to visually monitor study progress and assess potential for respondent bias. This is akin to tracking patient accrual rates into a clinical trial over time to assess screening yield and generalizability of the study population.…”
Section: Discussionmentioning
confidence: 90%
“…Decision aids are a central component of SDM but do not presently exist for the relevant adult vaccinations. Multiple previous surveys have demonstrated substantial physician knowledge gaps about specific adult vaccines [9][10][11][12] ; decision aids could bridge this gap and reduce the time needed for discussion. In our study, substantial numbers of physicians reported needing additional guidance on what SDM means and how to explain it to patients as well as not knowing how to implement SDM, corresponding to previous literature demonstrating lack of self-efficacy or familiarity with SDM as major barriers to implementation of such recommendations.…”
Section: Deal Of Variation In How Shared Decision-making Is Carried Outmentioning
confidence: 99%
“…Our data highlight the challenges SDM recommendations for adult vaccination pose for primary care physicians given the increasing expectations for SDM for multiple clinical decisions, the complexity of the patients they are seeing, and the limited time they have for primary care visits. Given the fact that physicians' knowledge about changing vaccine recommendations, insurance coverage for vaccines with different types of recommendations, and the risks and benefits for patient subgroups is likely to be limited based on previous data from national surveys, [9][10][11][12] the development of decision support tools for specific vaccine decisions will be important in guiding SDM vaccine discussions. Our data also emphasize the need for decision software to be aligned with SDM recommendations; if not aligned, such systems may default to either routine recommendations or indicate a vaccine is not recommended.…”
Section: Deal Of Variation In How Shared Decision-making Is Carried Outmentioning
confidence: 99%
See 1 more Smart Citation